Efektivitas penerimaan pajak Mineral bukan logam dan batuan - Dedy Fajrul; Ilham; Nurul Afifah (PT Bone Jaya Kreatif, 2022)
Mineral resources as one of the natural wealth owned by the Indonesia. Non-metallic and rock mineral resources in this case are classified into three types: type A, type B and type C and there are fundamental differences between the three types. In this research focused on excavation type C which is used as industrial raw material. Type C is a tax object that is regulated in Law Number 28 Year 2009 on regional tax and regional levies in article 60. This study aims to determine the effectiveness of tax revenues retrieval and processing of mineral and non-metal mineral deposits in Pangkep. This research uses Quantative approach with descriptive data analysis technique by describing data in the form of target and realization of revenue in 2014-2016 in Pangkep. The results of this study indicate that the effectiveness of non-metallic mineral taxes and rocks in 2014-2016 in Pangkep is considered very effective